2009 10th Annual Non-Volatile Memory Technology Symposium (NVMTS) 2009
DOI: 10.1109/nvmt.2009.5429783
|View full text |Cite
|
Sign up to set email alerts
|

Reliability characterization of Phase Change Memory

Abstract: Phase Change Memory (PCM) has emerged as an attr~ctive candidate for next-generation non-volatile memory devices, For these applications, reliability is determined by the abili~y to retain the state of data in the device and support a specified number of re-writes without failure. In PCM technologies, retention is limited by the meta-stable amorphous state of the cell. For cycling endurance (re-writes), failure occurs due to either void formation in the active material or contamination of the heating element o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 12 publications
1
34
0
Order By: Relevance
“…An early report showed that every lOx increase in pulse energy results in 1000x lower endurance [13], [11]. Recent measurements of failure rates on fabricated PCM chips showed similar results -lOx more failures were observed when a cell is 60% overheated [7]. While strong systematic process variations (PV) might be miti gated through circuit design, e.g., current provision [28] or customized write circuit [15], there are still non-negligible variations at the chip level.…”
Section: B Process Variationmentioning
confidence: 85%
“…An early report showed that every lOx increase in pulse energy results in 1000x lower endurance [13], [11]. Recent measurements of failure rates on fabricated PCM chips showed similar results -lOx more failures were observed when a cell is 60% overheated [7]. While strong systematic process variations (PV) might be miti gated through circuit design, e.g., current provision [28] or customized write circuit [15], there are still non-negligible variations at the chip level.…”
Section: B Process Variationmentioning
confidence: 85%
“…Data retention, endurance, program and read disturbs are some of the basic reliability aspects that have been investigated recently [12] [18]. In this paper we assume that there exist failing mechanisms or process variations causing some PRAM cells fail earlier than others [9]. Since PCM may have failures at some point, we need a scheme to detect and correct errors in PRAM.…”
Section: Reliability Lifetime and Eccmentioning
confidence: 99%
“…To keep track of the wear-out status of PRAM, we use the number of write-accesses to PRAM as a metric. We assume that the raw bit error rate increases as PRAM ages [9]. Therefore, we gradually increase the strength of ECC protection by allocating more ECC bits when PRAM is gradually worn out.…”
Section: Adaptive Ecc Managementmentioning
confidence: 99%
“…However, PCRAM is still challenging for its reliability enhancement [4,5]. Recently, some methods have been proposed to improve the reliability of PCRAM by studying the material characteristics and improving the fabrication process.…”
Section: Introductionmentioning
confidence: 99%